Home infusions of natalizumab for people with multiple sclerosis: a pilot randomised crossover trial. Issue 8 (21st July 2021) - Schultz, Timothy J.; Thomas, Anne; Georgiou, Paul; Juaton, Mahasen S.; Cusack, Lynette; Simon, Lorraine; Naidoo, Kerisha; Webb, Kevin; Karnon, Jonathan; Ravindran, Janakan
Abstract: Objective: The delivery of healthcare at home has expanded to intravenous infusions of monoclonal antibodies. A recently developed model of care for home infusions of natalizumab for people with relapsing‐remitting multiple sclerosis was evaluated. This pilot study of home infusions of natalizumab and usual care (attendance in a hospital out‐patients' clinic) compared safety, feasibility, patient satisfaction, effectiveness and costs. Methods: In this randomised AB/BA crossover trial, 37 adults were randomised to usual care ( n  = 19) or home infusions ( n  = 18). After three infusions, patients crossed over to the alternate treatment for another three infusions. Patient safety outcomes and adherence, satisfaction, quality of life, disability and costs were compared. Results: No adverse events were recorded from 207 infusions from 35 patients across both home and clinic infusions. There was no difference in adherence ( p  = 0.71) and infection rates ( p  = 0.84) between home and clinic settings. Satisfaction with "convenience" of home infusions was significantly greater ( p  = 0.008) but there were no differences in quality of life measures. Excluding pharmacy, costs were A$74 lower per infusion at home, including A$16 of patients" out‐of‐pocket costs. Interpretation: There were no differences in safety and effectiveness between clinic and home infusions of natalizumab. The home infusions were shown to be feasible, more convenient and less expensive than usual care. Larger scale studies are required to verify these preliminary findings, particularly around safety and management of hypersensitivity adverse events in the home setting and for equivalence of clinical outcomes.